Pilostyles maya, a novel species from Mexico and the first cleistogamous species in Apodanthaceae (Cucurbitales) - Ortega-González, Pactli F.; Rios-Carrasco, Sandra; González-Martínez, César Adrián; Bonilla-Cruz, Natalia; Vázquez-Santana, Sonia (Phytotaxa, 2020)
Pilostyles maya (Apodanthaceae), a new Mexican species endemic to the Yucatán Peninsula, is described and illustrated. Ecological, geographical, molecular, and morphological evidence are provided to support the new species status of Pilostyles maya. A molecular phylogenetic analysis based on the mitochondrial matR and nuclear 18S genes recovered P. maya as sister to P. mexicana. It is distinguished from its congeners by having cleistogamous, hermaphroditic flowers, tepals with ciliate margins and specificity on a Bauhinia host. These traits are novel for the genus and family. We propose that P. maya be listed as Critically Endangered due to its small known area of distribution and threats from deforestation in its area of occurrence.